REPRESENTASI STRATEGI KEKUASAAN SIMBOLIK TUTURAN GURU DALAM MEMBUKA PEMBELAJARAN - Siti Nur Afifatul Hikmah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Representation as a picture of the existence of a thing. In this case the representation of teachers in learning has power. The symbolic power of the teacher's speech in learning makes the teacher a person or group that holds the power of symbols. The symbolic power exercised by the teacher in learning cannot be separated from speech acts in the form of orders, invitations, advice, praise, questions, explanations and information. This research method uses a qualitative approach with the type of field research.